A lousa digital interactiva na rede pública municipal de ensino em Aracaju : uma tecnologia digital de informação e comunicação como veetor de transformação cultural - Pereira, Max Augusto Franco (2015)
This paper investigates the potential of Interactive Digital Whiteboards (LDI) installed in schools Municipal Public Network Aracaju Teaching (RPMEA), in order to find the process of using this Digital Technology of Information and Communication by teaching professionals in schools of elementary school. The research is based on survey of the technical and operational characteristics of the Interactive Digital Whiteboard, Epson models BrightLink® 450 / 455Wi, as a support tool for teaching and learning in the classroom; in the study of genealogy of the classroom as a social environment meanings of the education process; the significance and interdependence between culture and education and the presentation of the transformation of mass culture to the culture of digital media to the cyberculture, as new paradigm of experiences and subjectivities in conflict with the traditional model of school education, to identify and analyze which are the variables that make it difficult and contribute to the disuse of LDI in Elementary Education Municipal Schools in RPMEA, investigated between March 2012 and December 2014. The research methodology as the goal is exploratory and explanatory, of quantitative and qualitative approach, the nature of documentary sources and field raised at the headquarters of SEMED and five RPMEA schools selected, using the systematic gathering of technical data through observation, benchmarking and textual and photographic records of installation conditions and the LDI the technical support of networks and the associated infrastructure, s well as semi-structured interviews with professionals crowded in administration, technical and pedagogical support of SEMED and school units RPMEA. The analysis of the sources followed the line of the hypothesis, which was confirmed with the execution of the defined goals, allowing conclusive answer to the research problem that the variables that hinder the implementation of objectives of LDI and introduction of the Digital Media Culture in RPMEA are the result of the contradictions between the political and educational aspirations of the SEMED education planning, requirements made available for infrastructure and technical support in EMEF and the inconsistency of the training program for teaching professionals.